Construction of a densely poly(ethylene glycol)-chain-tethered surface and its performance - Nagasaki, Yukio (Polymer journal, 2011)
Non-biofouling surfaces constitute one of the most important subjects in sensitively and selectively detecting biomolecular events. Poly(ethylene glycol) (PEG) chains tethered on substrate surfaces are well known to reduce non-biofouling characteristics. Protein adsorption onto a PEG-chain-tethered surface is strongly influenced by the density of the PEG chain and is almost completely suppressed by the successive treatment of longer PEG chains (5 kDa) followed by the treatment of PEG (2 kDa; mixed-PEG-chain-tethered surface) because of a significant increase in PEG chain density. To modify versatile substrate surface, PEG possessing pentaethylenehexamine at one end (N6-PEG) was prepared via a reductive amination reaction of aldehyde-ended PEG with pentaethylenehexamine. Using N6-PEG, antibody/PEG co-immobilization was conducted on a substrate possessing active ester groups. After the antibody was immobilized on the surface, PEG tethered chains were constructed surrounding the immobilized antibody. It is interesting to note that the PEG-chain-tethered functions not only as a non-fouling agent but also improves immune response. The hybrid surface was also applied to oligo DNA immobilization. The oligo DNA/PEG hybrid surface improved hybridization, retaining its non-fouling ability. Densely packed PEG tethered chains surrounding antibodies and/or oligo DNA improved their orientation on the surface. Thus, this material is promising as a high-performance biointerface for versatile applications. Protein adsorption on the poly(ethylene glycol) (PEG)-tethered-chain surface was almost completely suppressed by successive treatment of longer PEG chain followed by treatment of PEG (2 kDa; mixed-PEG tethered-chain surface) because of significant increase in PEG chain density. Using pentaethylenehexamine-ended PEG, which was newly designed by ourselves, antibody/PEG and oligoDNA/PEG co-immobilizations were carried out. The PEG tethered chain was found to work not only as a non-fouling character but also as an improvement in orientation of biomolecules. Thus, it is promising as a high-performance biointerface for versatile applications.